Our treatment experience in poisoning with calcium channel blockers: A series of twelve cases - Talay, Mehmet Nur; Orhan, Özhan; Özbek, Mehmet Nuri; Kanğın, Murat; Turanlı, Eşe Eda (Brieflands, 2024)
Background: Intoxications with cardiovascular system drugs constitute a small percentage of all poisoning cases. Calcium Channel Blockers (CCBs) are the most common drug poisoning in this group. Objectives: We aimed to evaluate the effectiveness of treatments for CCB poisoning and add to the current body of literature by outlining the clinical treatments we employ for bradyarrhythmia, hypotension, and resistant vasodilation resulting from CCB poisoning, as well as sharing our clinical insights in this field. Methods: Twelve patients, ranging in age from 1 month to 18 years, were admitted to the Tertiary Paediatric Intensive Care Unit (PICU) for treatment of medication poisoning related to the CCB group. Patients who ingested several drugs that caused CCB were not allowed to participate in the trial. Results: Twelve patients were followed up in the PICU due to poisoning with CCB group drugs. Of the patients, 7 were male and 5 were female. Five of the patients had taken CCB medication with the purpose of committing suicide, and 7 of them accidentally. All of the patients who received CCB to commit suicide had taken verapamil. Five patients whose hypotension and bradycardia continued were administered inotropes. In addition to PI, calcium gluconate, intravenous lipid, glucagon, insulin, bicarbonate, and methylene blue were given as therapy to our symptomatic patients. Plasmapheresis was applied to a patient who was hospitalized in the PICU due to a sudden loss of consciousness. Conclusions: In the management of patients with CCB poisoning, the use of hyperinsulinemia euglycemia, intravenous lipid emulsion treatment, glucagon treatments, and treatments including methylene blue and extracorporeal life support should be considered in cases of resistant hypotension, bradycardia, and coma in the early period.
Keywords: Calcium Channel Blockers; Children; Poisoning